The Effect of Teacher Professional Competence and Learning Facilities on Student Achievement - Rusmin Husain; Amin Otoni Harefa; Pandu Adi Cakranegara; Mulyawan Safwandy Nugraha; Ul'Fah Hernaeny (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to find out and obtain objective information about the effect of teacher professional competence and student learning facilities on learning achievement in class X SMA Negeri 1 Teluk Keramat, Sambas Regency. The method used in this research is descriptive quantitative method with the Expost Facto approach. with the form of research used in this study is a comparative causal study. The data analysis technique from the results of this study is descriptive statistics used to describe the data for each variable and regression analysis is used for hypothesis testing. The results of this study indicate that (1) the professional competence of teachers is included in the good criteria and a total score of 9770 is obtained. Student learning motivation is included in the high criteria and a total score of 5535 is obtained. The conclusion of this study is that the variable of teacher professional competence has a positive and significant influence on the results. student learning that is equal to 31.13%, and the variable of student learning motivation has a positive and significant influence on learning outcomes that is equal to 4.41%, while the variables of teacher professional competence and student learning motivation together have a positive and significant influence on learning outcomes. students, namely 56.9%.